2007
DOI: 10.1002/mrm.21215
|View full text |Cite
|
Sign up to set email alerts
|

T2‐prepared SSFP improves diagnostic confidence in edema imaging in acute myocardial infarction compared to turbo spin echo

Abstract: T 2 -weighted MRI of edema in acute myocardial infarction (MI) provides a means of differentiating acute and chronic MI, and assessing the area at risk of infarction. Conventional T 2 -weighted imaging of edema uses a turbo spin-echo (TSE) readout with dark-blood preparation. Clinical applications of darkblood TSE methods can be limited by artifacts such as posterior wall signal loss due to through-plane motion, and bright subendocardial artifacts due to stagnant blood. Single-shot imaging with a T 2 -prepared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
255
0
1

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(261 citation statements)
references
References 19 publications
5
255
0
1
Order By: Relevance
“…All imaging data for each slice were acquired during a single cardiac cycle. During the subsequent cardiac cycle, a low flip angle single-shot gradient-echo acquisition was used to acquire proton density information for the same slice, which was used to normalize signal intensity, as described previously (9).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All imaging data for each slice were acquired during a single cardiac cycle. During the subsequent cardiac cycle, a low flip angle single-shot gradient-echo acquisition was used to acquire proton density information for the same slice, which was used to normalize signal intensity, as described previously (9).…”
Section: Methodsmentioning
confidence: 99%
“…The T 2 /T 1 of edematous myocardium (60 -65 ms/1197 ms) (9,10) is higher than that of normal myocardium (45-50 ms/1011 ms) (9,10), and, therefore, edematous tissue should appear brighter on a T 2 /T 1 -weighted image when compared with normal myocardium.…”
mentioning
confidence: 99%
“…Unfortunately, T2-weighted dark-blood TSE sequences are prone to image artifacts such as signal intensity variations caused by the use of phased-array coils, bright rim artifacts next to the endocardium caused by insufficient suppression of the signal from slow flowing blood, or posterior wall signal loss caused by through-plane motion of the dark-blood prepared slice out of the imaging slice in the case of improper timing [10 -12]. Consequently, Kellman et al showed that T2-weighted dark-blood TSE imaging was either non-diagnostic or incorrect in 29 % of patients with AMI [13]. Recently, a quantitative T2 mapping technique that overcomes these limitations has been introduced for the evaluation of myocardial edema [14].…”
mentioning
confidence: 99%
“…In part this is because even for a given patient, there are many other parameters which influence signal intensity and thus a consistent absolute threshold value cannot be utilized. Second, artifacts related to motion, volume averaging, and inability to null areas of static blood can result in areas of increased T2W signal [7,10]. Realizing these limitations, Joshi and colleagues took special care to measure the signal intensity in the epicardial half of the myocardium (i.e.…”
mentioning
confidence: 99%